Estimated Global, Regional, and National Disease Burdens Related to Sugar-Sweetened Beverage Consumption in 2010. Issue 8 (25th August 2015) - Singh, Gitanjali M.; Micha, Renata; Khatibzadeh, Shahab; Lim, Stephen; Ezzati, Majid; Mozaffarian, Dariush
<x xml:space="preserve">Abstract</x> Background— Sugar-sweetened beverages (SSBs) are consumed globally and contribute to adiposity. However, the worldwide impact of SSBs on burdens of adiposity-related cardiovascular diseases (CVDs), cancers, and diabetes mellitus has not been assessed by nation, age, and sex. Methods and Results— We modeled global, regional, and national burdens of disease associated with SSB consumption by age/sex in 2010. Data on SSB consumption levels were pooled from national dietary surveys worldwide. The effects of SSB intake on body mass index and diabetes mellitus, and of elevated body mass index on CVD, diabetes mellitus, and cancers were derived from large prospective cohort pooling studies. Disease-specific mortality/morbidity data were obtained from Global Burden of Diseases, Injuries, and Risk Factors 2010 Study. We computed cause-specific population-attributable fractions for SSB consumption, which were multiplied by cause-specific mortality/morbidity to compute estimates of SSB-attributable death/disability. Analyses were done by country/age/sex; uncertainties of all input data were propagated into final estimates. Worldwide, the model estimated 184 000 (95% uncertainty interval, 161 000–208 000) deaths/y attributable to SSB consumption: 133 000 (126 000–139 000) from diabetes mellitus, 45 000 (26 000–61 000) from CVD, and 6450 (4300–8600) from cancers. Five percent of SSB-related deaths occurred in low-income, 70.9% in middle-income, and 24.1% in high-income countries. Proportional mortality attributable to SSBs ranged from <1% in Japanese >65 years if age to 30% in Mexicans <45 years of age. Among the 20 most populous countries, Mexico had largest absolute (405 deaths/million adults) and proportional (12.1%) deaths from SSBs. A total of 8.5 (2.8, 19.2) million disability-adjusted life years were related to SSB intake (4.5% of diabetes mellitus–related disability-adjusted life years). Conclusions— SSBs are a single, modifiable component of diet that can impact preventable death/disability in adults in high-, middle-, and low-income countries, indicating an urgent need for strong global prevention programs.